Analysis SWOT to Establish Marketing Strategies at PT.Hilon Indonesia Bandar Lampung Branch - Fitriyani, Fika (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
This SWOT analysis aims to formulate an effective marketing strategy for PT. Hilon Indonesia Bandar Lampung Branch. Through identifying strengths, weaknesses, opportunities, and threats, it was found that the company has strengths in high-quality products, good reputation, and advanced technology. However, companies also face disadvantages such as high production costs and dependence on suppliers. Opportunities that can be exploited include market growth and product innovation, while the main threats come from intense competition and pressing raw material prices. Recommended strategies include product diversification, increasing operational efficiency, market expansion, brand strengthening, and partnership strategies. The implementation of these strategies is expected to increase competitiveness and support PT's sustainable growth. Hilon Indonesia Bandar Lampung Branch.